Strategic analysis of climate change and food security in Malaysia - Mohd Azman, Ahmad Luqfi Nulhakim; Abdullah, Nurfatihah Aqilah; Ninam Shah, Siti Khadijah; Puteh, Fadilah (Faculty of Administrative Science and Policy Studies, 2023)
Climate change is a natural process that occurs when there are changes in the weather temperature, amount of rainfall, and wind. According to the United Nations (2021), climate change happens when there is a high amount of greenhouse gas emissions. Human activities such as power generation through the burning of fossil fuels, manufacturing, deforestation for development projects, transportation, food production, and others contribute to the increase of greenhouse gases globally. This article focused mostly on the Malaysian Ministry of Agriculture and Food Industry (MAFI) to address climate change and food security. This article adopted several key strategic management techniques such as PEST analysis, a custom-made internal audit analysis, and SWOT analysis technique for the purpose of performing the internal and external analysis of Malaysia climate change and food security. This serves as a tool for identifying issues relating to food security. The TOWS matrix and BOS were then utilised to generate many viable recommendations. This article is useful in giving information on food security in Malaysia as well as appropriate recommendations that relevant stakeholders may implement.